Vertical and Horizontal Heat Transfer from a Limited-Area Heat Source - Glendening, John W. (1992)
This paper investigates the heat budgets produced by a limited area heat source, as modelled in a large-eddy simulation. The physical prototype is a series of Arctic leads, breaks in the Arctic pack ice which allow relatively warm ocean water to contact the cold atmosphere. This idealized case represents periodic inhomogeneous surface conditions. Local budgets of temperature and vertical turbulent heat flux will be compared to their domain averaged values. . Air-sea interaction, Boundary layer, Coupled models.